Private Positionsdaten und polizeiliche Aufklärung von Diebstählen Rechtliche, kriminalistische und technische Perspektiven - Fährmann, Jan; Görlitz, Gudrun; Matzdorf, Christian Friedrich; Vollmar, Alexander (HWR Berlin Forschung, 2023)
This anthology is based on the interdisciplinary project 'FindMyBike: legal and technological concepts for the transmission of time-based geodata on a criminological and administrative science basis'. In this project, technological concepts for the location of theft-prone objects were developed and applied in cooperation with the police to facilitate the prosecution of such crimes and the recovery of the stolen objects using the example of bicycle theft. Its highly scientific approach with intensive references to police practice and the inclusion of protection and criminal police expertise in theory and field tests generate results that form the basis for further research.